Research progress and development trend of heat-resistant aluminum alloys in aerospace industry - CHEN Han; WU Pengcheng; ZHANG Tao; KUANG Shuqian; ZHANG Liangxian; ZHAO Ke; LIU Jinling (Journal of Aeronautical Materials, 2024)
The development of supersonic aircraft has created an urgent demand for heat-resistant aluminum alloy that can serve at the temperatures range from 300 ℃ to 500 ℃. However，the high-temperature mechanical properties of heat-resistant aluminum alloys are still unable to meet practical application requirements. Therefore，further research is needed from the aspects of material composition design and microstructure control to improve the comprehensive mechanical properties of heat-resistant aluminum alloys. In this paper, the research progress of heat-resistant aluminum alloys is reviewed from the aspects of microalloying design and eutectic alloys，and the development trend of heat-resistant aluminum alloys is prospected. The article first systematically introduces the development history and research status of Al-Sc，Al-Cu，Al-Si，and Al-Mg heat-resistant aluminum alloys，focusing on the microalloying design ideas of heat-resistant aluminum alloys，as well as the effects of transition metal elements and rare earth elements on precipitation phases，microstructure，and mechanical properties. Subsequently，the development status of heat-resistant eutectic aluminum alloys in Al-Fe，Al-Ni，Al-Ce，and Al-Si systems is comprehensively summarized，with a focus on the important role of rapid solidification technology and additive manufacturing technology in promoting the development of heat-resistant eutectic aluminum alloys. Finally，the main problems faced in the development and application of new heat-resistant aluminum alloys are analyzed，and the development trends of future research on heat-resistant aluminum alloy is discussed from the perspectives of data-driven composition design，high-throughput experimental verification，engineering application research，and standard system construction.